2015
DOI: 10.1038/srep14447
|View full text |Cite
|
Sign up to set email alerts
|

Small cell lung cancer transformation and T790M mutation: complimentary roles in acquired resistance to kinase inhibitors in lung cancer

Abstract: Lung cancers often harbour a mutation in the epidermal growth factor receptor (EGFR) gene. Because proliferation and survival of lung cancers with EGFR mutation solely depend on aberrant signalling from the mutated EGFR, these tumours often show dramatic responses to EGFR tyrosine kinase inhibitors (TKIs). However, acquiring resistance to these drugs is almost inevitable, thus a better understanding of the underlying resistance mechanisms is critical. Small cell lung cancer (SCLC) transformation is a relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 26 publications
2
62
0
Order By: Relevance
“…In the current case, it was nearly 16 months to second progression. Acquired resistance is mostly seen after 9 to 14 months of EGFR-TKI therapy (8). Similarly, in the present case, tumor progression occurred in the 13th month of erlotinib therapy.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In the current case, it was nearly 16 months to second progression. Acquired resistance is mostly seen after 9 to 14 months of EGFR-TKI therapy (8). Similarly, in the present case, tumor progression occurred in the 13th month of erlotinib therapy.…”
Section: Discussionsupporting
confidence: 75%
“…In this instance, some specific genomic changes may have a role in SCLC transformation. In a patient with EGFR mutation, while liver metastasis showing SCLC phenotype had PTEN M2641, metastasis of adenocarcinoma phenotype didn't have this mutation (8). Sequist et al (18) reported a PI3K-AKT mutation with SCLC transformation, but a presence of only 5% of NSCLC cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings support the concept of a reciprocal relationship between SCLC transformation and T790M mutation. 4 So far, there has been only one case report on the presence of T790M mutation in the primary lung adenocarcinoma that had transformed to SCLC. 5 Because adenocarcinoma and SCLC originate from the same stem cell, such rare transformation that preserves the EGFR TKI resistance property of adenocarcinoma is possible.…”
mentioning
confidence: 99%